Lessons Learned from an Intergenerational Model that Engages Fathers and Sons to Prevent Violence Against Women and Children in the Kurdistan Region of Iraq - Francar, Jessica Francar; Ragonese, Cody Ragonese (Sulaimani Journal for Humanities, 2026)
This study describes the impact of an intergenerational program, piloted by SEED Foundation with the support of Equimundo, in the Kurdistan Region of Iraq (KRI) from 2021-2023, which engages men and boys as supporters of gender equality, shifts harmful beliefs about women, helps to reduce intergenerational violence, and fosters healthy relationships within the home. The program engaged members of the host community, internally displaced persons, and Syrian refugees across Erbil, Sulaimani, and Duhok. SEED Foundation led the implementation of the pilot program in 2022-2023 with a total of 215 participants (96 fathers and 119 sons). Drawing from quantitative and qualitative results from the intervention’s evaluation, both the father and son program participants reported statistically significant increases in levels of knowledge regarding types of violence, attitude shifts that reject normalized justifications of violence, and an increase of behaviors related to emotional regulation. Results from fathers show more self-efficacy and self-reported behaviors of positive parenting and attitudes that welcome shared decision-making in the home. The evaluation with program participants and their wives/mothers highlights the unquantifiable impact of the program in strengthening family relationships and preparing fathers and sons to embody non-violent and caring notions of masculinity. This intergenerational program is a pertinent example of new directions for social work and exemplifies an approach wherein social workers can address violence within families and meaningfully engage men and boys alongside interventions that work directly with women and girls, to address social issues from a variety of different perspectives.
Keywords: Violence against women; intergenerational approach; nonviolence; healthy relationships; GBV